2022
DOI: 10.1186/s12935-022-02461-w
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis combined with experiments explores the oncogenic role of spindle apparatus coiled-coil protein 1 (SPDL1)

Abstract: Background The function of spindle apparatus coiled-coil protein 1 (SPDL1) as a cancer-promoting gene has been reported in a number of studies. However, the pan-cancer analysis of SPDL1 is still lacking. Here, we performed this pan-cancer analysis to evaluate the expression and prognostic value of SPDL1 and gain insights into the association between SPDL1 and immune infiltration. Methods In this study, based on the datasets of The cancer genome atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…This included down-regulation of spindle apparatus coiled-coil protein 1 (SPDL1), and fatty acid binding protein 1 (FABP1), along with the up-regulation of OAS1 and REN, suggesting complex interactions between antioxidants and mycotoxins. In the kidney cytoplasmatic fraction, SPDL1 contributes to the maintenance of genomic stability during cell division (Song et al 2022), ensuring proper development and function of renal cells. FABP1, primarily expressed in the liver but also found in renal proximal tubular cells, is involved in the PPAR signalling pathway ( Figure S25 ), through uptake, transport, and utilization of fatty acids, which are essential for energy production and membrane synthesis in renal cells (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This included down-regulation of spindle apparatus coiled-coil protein 1 (SPDL1), and fatty acid binding protein 1 (FABP1), along with the up-regulation of OAS1 and REN, suggesting complex interactions between antioxidants and mycotoxins. In the kidney cytoplasmatic fraction, SPDL1 contributes to the maintenance of genomic stability during cell division (Song et al 2022), ensuring proper development and function of renal cells. FABP1, primarily expressed in the liver but also found in renal proximal tubular cells, is involved in the PPAR signalling pathway ( Figure S25 ), through uptake, transport, and utilization of fatty acids, which are essential for energy production and membrane synthesis in renal cells (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…stability during cell division(Song et al 2022), ensuring proper development and function of renal cells. FABP1, primarily expressed in the liver but also found in renal proximal tubular cells, is involved in the PPAR signalling pathway (FigureS25), through uptake, transport, and utilization of fatty acids, which are essential for energy production and membrane synthesis in renal cells(Wang et al 2015).The down-regulation of SPDL1 and FABP1 expression might indicate disruptions in the cell division processes and lipid metabolism, respectively, while the up-regulation of REN suggests potential involvement in the urea cycle.…”
mentioning
confidence: 99%
“…GSVA showed that a number of pathways associated with malignancy were substantially upregulated in the low-risk group. These included hypoxia (43)(44)(45), the p53 pathway (44,46), KRAS signaling (47,48), TGF signaling MTOR signaling pathways (49,50), mitotic spindle (51), and other processes. All of the above data suggest that many pathways may be involved in the underlying mechanisms responsible for the poor prognosis of LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous study, the pathological assessment of staining was performed using the CPS, and CPS ≥1 was considered as positive [ 32 , 33 ]. We used the semi-quantitative scoring method according to a previous study by multiplying the score of staining intensity and the score of positive cells for FTH1 [ 34 ]. The low expression was defined as the scores from 0 to 6, and the high expression was defined as the scores from 7 to 12.…”
Section: Methodsmentioning
confidence: 99%